AKUNTANSI PENJUALAN KREDIT DITINJAU DARI ASPEK KEPERILAKUAN PADA PT DWI SURYA PERKASA - Nur Ainia; Purwanto (Ekomania, 2023)
This study aims to understand how the influence of the credit sales accounting system on behavioral aspects in the scope of attitudes, motivations and emotions at PT Dwi Surya Perkasa. The type of research that the author does is associative quantitative method research. Data collection was carried out in this study by using a questionnaire and respondents were required to answer all of them. The results of the research and the hypotheses developed by the researcher indicate that the behavioral aspects, attitudes and motivations have a positive and significant impact on the use of the credit sales accounting system, this is because the company has SOPs that work well on credit sales which are set as the basis for employees in doing work. . This research has been carried out using scientific procedures, but there are still many limitations, especially behavioral aspects that affect the application of the credit sales accounting system consisting of three variables of attitude, motivation and emotion, but there are still many other aspects that can affect the credit sales accounting system and sometimes the sample gives no answer. reflect the real situation.